2011
DOI: 10.1074/jbc.m110.200311
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of STAT3 Protein-mediated Cellular Respiration by SIRT1 Protein

Abstract: In mammals, the transcriptional activity of signal transducer and activator of transcription 3 (STAT3) is regulated by the deacetylase SIRT1. However, whether the newly described nongenomic actions of STAT3 toward mitochondrial oxidative phosphorylation are dependent on SIRT1 is unclear. In this study, Sirt1 gene knock-out murine embryonic fibroblast (MEF) cells were used to delineate the role of SIRT1 in the regulation of STAT3 mitochondrial function. Here, we show that STAT3 mRNA and protein levels and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 73 publications
3
88
0
Order By: Relevance
“…Bernier et al (22) reported negative regulation of STAT3 protein-mediated cellular respiration by SirT1 in murine embryonic fibroblast cells (21), and a previous study provided further support for these results (41). As previously demonstrated, pSTAT3 stimulated expression of the STAT3 gene [unphosphorylated STAT3 (U-STAT3)], which exerted persistent activity (42).…”
Section: A B C Dsupporting
confidence: 57%
See 1 more Smart Citation
“…Bernier et al (22) reported negative regulation of STAT3 protein-mediated cellular respiration by SirT1 in murine embryonic fibroblast cells (21), and a previous study provided further support for these results (41). As previously demonstrated, pSTAT3 stimulated expression of the STAT3 gene [unphosphorylated STAT3 (U-STAT3)], which exerted persistent activity (42).…”
Section: A B C Dsupporting
confidence: 57%
“…Based on the known roles of SirT1 and STAT3 in oxidative stress, it was hypothesized that there is crosstalk between the two molecules during oxidative stress. Interactions between SirT1 and STAT3, which have versatile roles in various microenvironments, had previously been identified (20,21). However, whether or not there was crosstalk between the two molecules during oxidative stress in RPEs and what the mechanism of crosstalk was, remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the biochemical requirements of this pathway are still controversial (39), there is evidence that mitochondrial STAT3 may improve organelle performance and antagonize apoptosis during acute vascular injury (40), consistent with a non-transcriptional function of STAT3 in cellular responses (41). At variance with this paradigm, STAT3 induced by CypD depletion did not significantly accumulate in mitochondria, and its phosphorylation on Ser-727, a marker of the mitochondrial pool of the molecule (25,26), was not affected in CypD-targeted cells.…”
Section: Discussionmentioning
confidence: 67%
“…Confirming the specificity of this response, CypD targeting in different cell types did not affect STAT3 phosphorylation on Ser-727 (Fig. 5D), an activation marker of mitochondria-localized STAT3 (25,26).…”
Section: Signaling Requirements Of Cypd-directed Cellular Responsesanmentioning
confidence: 73%
See 1 more Smart Citation